The Underlying Tumor Genomics of Predominant Histologic Subtypes in Lung Adenocarcinoma - Caso, Raul (J Thorac Oncol, 2020)
INTRODUCTION: The purpose of the study is to genomically characterize the biology and related therapeutic opportunities of prognostically important predominant histological subtypes in lung adenocarcinoma (LUAD). METHODS: We identified 604 patients with stage I-III LUAD who underwent complete resection and targeted next-generation sequencing using the MSK-IMPACT platform. Tumors were classified according to predominant histologic subtype and grouped by architectural grade (lepidic [LEP], acinar or papillary [ACI/PAP], and micropapillary or solid [MIP/SOL]). Associations between clinicopathologic factors, genomic features, mutational signatures, and recurrence were examined within subtypes and, when appropriate, quantified using competing-risks regression, with adjustment for pathologic stage and extent of resection. RESULTS: MIP/SOL tumors had higher tumor mutational burden (p<0.001), fraction of genome altered (p=0.001), copy number amplifications (p=0.021), rate of whole-genome doubling (p=0.008), and number of oncogenic pathways altered (p<0.001), compared with LEP and ACI/PAP tumors. Across all tumors, mutational signatures attributed to APOBEC activity were associated with the highest risk of postresection recurrence: SBS2 (p=0.021) and SBS13 (p=0.005). Three oncogenic pathways (p53, Wnt, Myc) were altered with statistical significance in MIP/SOL tumors. Compared with LEP and ACI/PAP tumors, MIP/SOL tumors had a higher frequency of targetable BRAF-V600E mutations (p=0.046). Among ACI/PAP tumors, alterations in the cell cycle (p<0.001) and PI3K (p=0.002) pathways were associated with recurrence; among MIP/SOL tumors, only PI3K alterations were (p=0.049). CONCLUSIONS: These results provide the first in-depth assessment of tumor genomic profiling of predominant LUAD histologic subtypes, their associations with recurrence, and their correlation with targetable driver alterations in patients with surgically resected LUAD.